More Trees, More Poverty? The Socioeconomic Effects of Tree Plantations in Chile, 2001-2011 - Andersson, K.; Lawrence, D.; Zavaleta, J.; Guariguata, Manuel R. (Springer, 2016)
Tree plantations play a controversial role in many nations’ efforts to balance goals for economic development, ecological conservation, and social justice. This paper seeks to contribute to this debate by analyzing the socioeconomic impact of such plantations. We focus our study on Chile, a country that has experienced extraordinary growth of industrial tree plantations. Our analysis draws on a unique dataset with longitudinal observations collected in 180 municipal territories during 2001–2011. Employing panel data regression techniques, we find that growth in plantation area is associated with higher than average rates of poverty during this period.